International marketing - Ghauri, Pervez (McGraw - Hill, 2006)
"International Marketing 2/e" offers a truly global treatment of this exciting area of marketing - providing students with all the resources they need to grasp the complexities and issues when marketing across borders. Totally updated since its previous edition, the book now features more streamlined chapters, new chapters, totally new cases and a brand new text design, making it one of the most compelling and exciting books available.